Shaping Better Futures: Inside-Out Colombian English Language Teachers’ Gaps and Practices - Ingrit Juliana Díaz; Catalina Ipia Salinas; Liliana Cuesta Medina (Profile: Issues in Teachers' Professional Development)
This exploratory qualitative study reports gaps in the preservice teacher education and professional development of 15 English language teachers in a Colombian public university regarding their teaching knowledge and practice. Grounded theory was used to examine the data collected via focus groups and questionnaires, which were validated and triangulated. Findings reveal several teacher deficiencies, classified into three axes: language proficiency, teaching awareness, and teacher challenges. These tensions unveil imbalances between theory and practice, inefficient mentoring during the practicum stage, lack of classroom management skills for efficient teaching, and the need to revitalize and endorse information and communications technology education and use in the new classroom era. The article also offers a discussion on reconceptualizing teacher education.